ANALISIS YURIDIS PENANGANAN PERKARA TINDAK PIDANA PENCUCIAN UANG OLEH KORPORASI (ANALISIS TERHADAP PERMA NO. 13 TAHUN 2016 TENTANG TATA CARA PENANGANAN PERKARA TINDAK PIDANA OLEH KORPORASI) - Sahbana Pilihanta Surbakti; Bismar Nasution; Budiman Ginting; Madiasa Ablisar (USU LAW JOURNAL, 2019)
ABSTRACT The existence of rules of the Supreme Court (PERMA) No. 13 of 2016 On The handling of the matter a criminal offence by the Corporation (then known as Perma 13) was issued on the grounds that the Corporation as an entity or a legal subject its presence gives great contribution in enhancing economic growth and national development, but in reality the Corporation may also conduct various criminal acts (corporate crime) that carries the impact of losses against the State and society, that in fact the Corporation can be a place to hide the wealth of results the criminal act untouched legal proceedings in criminal liability (criminal liability). That many laws in Indonesia put the Corporation as the subject of a criminal offence may be subject to liability, but corporate law with the subject matter presented in criminal proceedings is still very limited, one of the reasons are the procedures and the procedures for inspection of the Corporation as the perpetrator of the crime is still unclear, it is therefore deemed necessary the presence of a guide for law enforcement officers in the handling of criminal cases committed by the Corporation. As for that being that became an issue in the formulation of the research is How the settings of the crime in the field of money laundering based on law No. 8 of 2010 About money laundering. This form of accountability for perpetrators of Crime money laundering according to law No. 8 of 2010 after the promulgation of the Perma No.13 of 2016 On The handling of the matter a criminal offence By the Corporation. Supreme Court rule number 13 of 2016 and use the approximation of legislation (the statute approach) of Act No. 8 of 2010 About money laundering. When examined related Arrangements in the field of money laundering crime under law No. 8 of 2010 Concerning the prevention and eradication of the crime of money laundering is arranged starting from article 3 up to article 9 of law No. 8 of 2010 on prevention and The Eradication Of Criminal Acts Of Money Laundering. PP TPPU article 6 of the ACT clearly states that a requirement can be dipidananya a corporation based on the crime of money laundering as referred to in article 3, article 4 and article 5, performed by the Corporation. takeover of the Corporation by the State of criminal with a replacement with the seizure of assets.   Keywords: Corporate, criminal act of money laundering, the Supreme Court Rules.